CONFOCAL MICROSCOPY OF BASAL CELL CARCINOMA – 2 CASE REPORTS - Leite, Inês (2011)
Reflectance Confocal Microscopy (RCM) allows a high resolution imaging for in vivo non-invasive evalu- ation of skin lesions. Confocal imaging diagnostic criteria for BCC are described and two case reports presented. The authors review this topic and emphasize the RCM role as a non-invasive tool for diagnosis, no disease assumption and monitoring of recurrences after treatment.KEYWORDS – Microscopy, Confocal; Carcinoma, Basal Cell.